Welfare and vulnerability: Findings from the first round of the Myanmar Household Welfare Survey - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
The first round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between December 2021 and February 2022 with 12,100 households. This report discusses its findings related to shocks, livelihoods, coping strategies and food security. We find that almost 1 in 5 households experience physical insecurity, more than 1 in 10 were negatively affected by climatic shocks, and 3 in 5 experienced sickness or death of household members in the past three months. Two thirds of households reported a lower income in the beginning of 2022 compared to 12 months earlier, indicating widespread impacts of the pandemic, the political crisis, and the ensuing economic crisis. Ninety percent of households applied at least one coping strategy to deal with lack of food or money during the past month. More than half of all households lowered food and non-food expenditures. A large number of households also used more dramatic coping strategies, including high-risk income generating activities (4 percent), children working (3 percent of households), migration (1 percent), or selling of the dwelling or land (1 percent). Even though data were collected in the beginning of 2022 after the monsoon harvest and thus a relatively favorable time of the year for food security, still 9 percent of the households did not have an adequate food consumption pattern and 4 percent suffered from moderate or severe hunger. Violent events in the township, self-reported physical insecurity, climatic and health shocks all are strongly associated with negative outcomes for income, coping and food security. Chin and Kayah state experienced high levels of violence and consistently perform worse across the range of welfare indicators considered.